Analisis Studi Kasus Krisis Komunikasi PT. Alpen Food Industry (Aice Ice Cream) Dan Serikat Buruh - Raissa Regina; Arubay Mahardhikawatie; Indra Kusumawardhana (LP2M, 2021)
PT. AFI or better known as the producer of AICE ice cream is a food sector company that is quite massive and well known by the public in Indonesia. The company with the tagline